Distinct transcriptomic landscapes of cutaneous basal cell carcinomas and squamous cell carcinomas - Jun Wan; Hongji Dai; Xiaoli Zhang; Sheng Liu; Yuan Lin; Ally-Khan Somani; Jingwu Xie; Jiali Han (Genes and Diseases, 2021)
The majority of non-melanoma skin cancer (NMSC) is cutaneous basal cell carcinoma (BCC) or squamous cell carcinoma (SCC), which are also called keratinocyte carcinomas, as both of them originate from keratinocytes. The incidence of keratinocyte carcinomas is over 5 million per year in the US, three-fold higher than the total incidence of all other types of cancer combined. While there are several reports on gene expression profiling of BCC and SCC, there are significant variations in the reported gene expression changes in different studies. One reason is that tumor-adjacent normal skin specimens were not included in many studies as matched controls. Furthermore, while numerous studies of skin stem cells in mouse models have been reported, their relevance to human skin cancer remains unknown. In this report, we analyzed gene expression profiles of paired specimens of keratinocyte carcinomas with their matched normal skin tissues as the control. Among several novel findings, we discovered a significant number of zinc finger encoding genes up-regulated in human BCC. In BCC, a novel link was found between hedgehog signaling, Wnt signaling, and the cilium. While the SCC cancer-stem-cell gene signature is shared between human and mouse SCCs, the hair follicle stem-cell signature of mice was not highly represented in human SCC. Differential gene expression (DEG) in human BCC shares gene signature with both bulge and epidermal stem cells. We have also determined that human BCCs and SCCs have distinct gene expression patterns, and some of them are not fully reflected in current mouse models.